Analisis Pengaruh Pendapatan Premi, Hasil Investasi dan Beban Klaim Terhadap Laba Perusahaan Asuransi Jiwa di Indonesia - Desirella desirella (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to examine whether the effect of premium income, the effect of investment returns, the effect of claim expenses on profits in Life Insurance companies registered with the Financial Services Authority (OJK). This study uses a descriptive research type quantitative approach, which is measured using multiple linear regression-based methods with SPSS 25. The population of this study is a conventional life insurance company registered with the Financial Services Authority (OJK) from 2015 to 2019. The sample was determined based on purposive sampling method, with a total sample of 25 life insurance companies. The data used in this study is secondary data. The data collection technique uses the documentation method through the official website www.ojk.go.id. The results of the study prove that (1) premium income has a significant positive effect on the profits of life insurance companies listed on the Financial Services Authority (OJK) for the 2015-2019 period, (2) investment returns have a significant positive effect on the profits of life insurance companies listed on the Financial Services Authority (OJK) for the 2015-2019 period, (3) claim expenses have a significant negative effect on the profits of life insurance companies listed on the Financial Services Authority (OJK) for the 2015-2019 period.